Letter (copy) - Citrine, Walter, 1887-1983
026-0007-001 International. WMC/WJB/AT/1218. 26th August, 1939. M. Pascual Tomas, Depute, 69 Rue de Taur, Toulouse, France. Dear Comrade Tomas, Supplementing our letter to you of the 15th August, we are now pleased to be able to inform you that if you will send us the money that you wish to be transferred to your wife, we can arrange to have it given to her through certain channels. We would, of course, see that the amount was paid to her in pesetas. Yours faithfully, General Secretary. 292/946/26/7